REFLECTION OF PROTAGONIST’S WORLDVIEW IN A CONTEMPORARY ARABIC NOVEL A CASE STUDY OF LATIN QUARTER (AL-HAYY AL-LATINI) - Nazemian, Houman; Hosseini, Abdollah (PEOPLE: International Journal of Social Sciences, 2018)
Latin Quarter is one of the famous novels of Suhail Idris, the well-known Lebanese novelist, short story writer, journalist and translator (1925-2008). This novel published in 1954, during a critical period in the middle east and in particular the Arab world. The confrontation between East and West is among the issues that have been reflected in many Arab novels during the 20th century. It is, in fact, part of a series of cultural and social problems in the Third world. In this paper, we have made an effort to elucidate the writer’s worldview in this novel. As such, his perspective on the Western and Eastern worlds, especially the conflicts between these two worlds, his idea of Paris, the alteration of his view about the world after making contact with the West, the cultural differences between the west and the east, and finally, the eastern protagonist’s excessive admiration for the west is explored in Latin quarter. Our methodology is Sociocriticism based on the Lucien Goldman's point of view. The results indicate the protagonist’s return to his native culture and city after all his adulations for the west. It seems that this novel reflects the author's experiences, and it is an invitation to Eastern youth to return to their homeland instead of emigration to the west and try to build their own countries and abide by their native traditions.